12.9k views
2 votes
2(4x - 3)=3(x+8)

The equation above is the problem I’m stuck on, I’m in algebra two and it’s been awhile since we’ve gone over this type of equation.

User Gregoire
by
5.0k points

1 Answer

6 votes

Answer:

x = 6

Explanation:

2(4x - 3) = 3(x + 8)

1. Distribute the 2 and 3 into the parentheses.

2(4x) + 2(-3) = 3(x) + 3(8)

= 8x - 6 = 3x + 24

2. Subtract 3x from both sides.

8x - 3x - 6 = 3x - 3x + 24

= 5x - 6 = 24

3. Add 6 on both sides.

5x - 6 + 6 = 24 + 6

5x = 30

4. Divide by 5.

5x ÷ 5 = 30 ÷ 5

x = 6

Hope that helps.

User Kushal Sharma
by
4.9k points